Investigating the Effect of Sex and Personality on Leader Emergence on an Initiating Structure Task - (:unkn) unknown (ISTANBUL UNIV, 2017)
The number of studies that have been conducted in various cultures in relation to leader emergence is limited. The aim of this study was to investigate the effects of sex and a pattern of self-monitoring, self-efficacy and dominance personality traits on leader emergence in Turkey. Two hundred and fifteen business students from a public university in Istanbul were categorized according to their sex and personality traits, and 60 of them were appointed to 4-person leaderless discussion groups randomly. Each group worked on an initiating structure type of task. After sessions were completed the participants rated other group members on a leadership perception scale. The results indicated that while there was no leader emergence difference between the sexes, the participants who were high on self-monitoring, self-efficacy and dominance personality traits emerged as leaders more than the participants who were low on all of these traits. These findings imply that both the culture and the task that has been worked on may have some important contributions in terms of leader emergence.
Keywords: Leader emergence; sex; self-monitoring; self-efficacy and dominance; ROLE CONGRUITY THEORY; SELF-EFFICACY SCALE; INDIVIDUAL-DIFFERENCES; GENDER-ROLE; IMPLICIT LEADERSHIP; PERCEPTIONS; DOMINANCE; WORK; METAANALYSIS; COMPETENCE